ASSESSMENT OF THE EFFICACY OF COMBINED EFFECT IMMUNOMODULATOR INOSINE PRANOBEX IN PREVENTING RESPIRATORY INFECTIONS IN CHILDREN WITH ALLERGIES - V.A. Bulgakova; I.I. Balabolkin; L.K. Katosova; M.S. Sedova; I.V. Zubkova (Педиатрическая фармакология)
Among children with allergies, particularly with bronchial asthma, patients susceptible to frequent acute respiratory infections make up a large group. In recent years, a strong focus has been on persistency of viruses and other pathogenic microorganisms in various areas of the respiratory tract, which leads to change in responsiveness of the organism and warrants the practicability of applying agents with a combined immunomodulating and antiviral effect. The purpose of this study was to assess the clinical and immunological efficacy of inosine pranobex in children with bronchial asthma and frequent respiratory infections. 37 children with atopic persistent moderate asthma at ages 4 to 15 were examined, 26 of which were administered inosine pranobex orally in prevention dosages at 50 mg/kg twice a day over 14 days. The control group was made up of 11 children who were on no immunopharmacological prevention course. Virus antigens in nasopharyngeal smear samples were identified, cytokine status and antibody immune response were studied. In the main group, 23 children (88,5%) were found to have the frequency and length of intercurrent acute respiratory viral infections decreased 1,5 times (p < 0,05) and the number of asthma attacks decreased 1,7 times (p < 0,05). The obtained results demonstrate the efficacy of preventing respiratory infections with inosine pranobex in children with bronchial asthma and other allergic diseases. Key words: acute respiratory infections, allergy, bronchial asthma, children, prevention, immunomodulators, inosine pranobex. (Pediatric Pharmacology. – 2010; 7(5):30-37)